Indigeneity and Blackness: Partners in the Struggles of Settler-Colonialism - Octavia Andrade-Dixon (Caribbean Studies Students' Union, 2020)
The North American continent, as it is known today, has experienced forced transformations over the past five hundred years. Through the hands of different European powers, what is known as Turtle Island by many was transformed into a radically different society. Colonizers built this territory through violent and unjust processes of dispossession and through the structural genocide of Indigenous people and the enslavement of African peoples. These processes are conceptualized as Settler-Colonialism and Trans-Atlantic Slavery. Through colonial violence, Indigenous identities have faced a barrage of Western values imposed on their everyday lives. Further, these impositions and shifts in societal structure have become internalised and therefore naturalized within Indigenous livelihood. For the descendants of slaves throughout the Americas, similar generational traumas have been enacted upon them by colonizing powers. Although the same perpetrators enacted these traumas, and in the same geographic space, they are kept separate within colonial rhetoric. However, I contest that these are not wholly separate entities, but processes that are in conversation with each other and hold strong similarities. Black and Indigenous communities are directly influenced by settler-colonial morality through the naturalization of heteropatriarchy and evangelical practises into community governance. This heteropatriarchy is then weaponized by the cis-gendered heterosexual (cishet) male population for their societal advancement and to regulate the actions of women and queer/two-spirit persons.